Analisis Pengaruh Pendidikan dan Pelatihan Sumber Daya Manusia Terhadap Kinerja Pegawai dengan Metode Regresi Linear Berganda di BKPSDM Kota Solok - Denny Rinaldi; Arie Prima; Syafwandi Syafwandi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Each employee receives education and training to obtain skills that suit the agency's needs. The aim of the research is to determine the analysis of the influence of the education variable (X1) and training variable (X2) of Human Resources on the employee performance variable (Y). The research location was carried out by researchers at BKPSDM Solok City using the Multiple Linear Regression method. The results of the research show that the HR education and training carried out by researchers has succeeded in finding that by increasing Human Resources training, employee performance will also increase in accordance with agency needs